Poda Na Lima Philosophy: The role of educators and the community in developing educational studies in Mandailing Natal - Hawa, Siti; Sinulingga, Neng Nurcahyati; Miftah, Muhammad; Naldi, Anri (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2023)
The Poda Na Lima philosophy, which aims to develop the study of Islamic education, needs to be maintained and preserved; therefore, the authors conducted this research using qualitative methods with a phenomenological approach. Observation data, interviews and documentation are data collection techniques, while informants as subjects of this research were 15 people from Mandailing Natal. Traditional figures, religious figures, community leaders, members, and documents related to history, culture, customs, and community life, such as books, articles, journals, reports, and mass media are sources of research data. Data analysis is used through presentation, reduction and conclusion. The research results show that Poda Na Lima has been developing an educational curriculum based on local content. The obstacle was that it had not been implemented optimally as part of developing the local content education curriculum there. It is due to a lack of coordination, socialization synergy, local government education, budget allocation, and human resource development for the community, especially the younger generation, regarding the importance of maintaining and preserving the philosophy. The authors concluded that with the development of local content educational curricula and local knowledge in the community, the local government needs to take policies to maintain and preserve the Poda Na Lima philosophy in Mandailing Natal.